The Pendok of the Surakarta Keris of Paku Buwono X: Art, Symbolism, and Social Status - Kuntadi Wasi Darmojo; Sunarmi Sunarmi; Sarwanto Sarwanto; Bagus Indrayana (International Journal Labs, 2025)
The pendok of the keris is one of the essential components of keris material culture, especially during the reign of Paku Buwono X in Surakarta. As an integral part of the keris, the pendok not only serves as a protective cover for the gandar, but also carries a symbolic role representing the aesthetics, social status, and spiritual values of the Javanese nobility. The presence of the pendok reflects refined artistic taste and serves as part of the identity marker system within the social structure of the royal court society. This article employs a qualitative approach using literature study methods to analyze the role, function, and meaning of the pendok keris within the cultural context of the Surakarta royal court, particularly during the golden era of art and metal craftsmanship under the reign of Paku Buwono X. This study shows that the pendok keris is not merely understood as a visual ornament, but also as a medium of cultural communication rich in symbols, life philosophy, and the social identity of its owner within traditional Javanese society.